Evaluation of English as a foreign language and its curriculum in Indonesia: a review - Mappiasse, Sitti Syamsinar (Canadian Center of Science and Education, 2014)
The most widely used language in research, business, politics and other areas of life in our contemporary world is the English language. The exploration of the world by the British people through colonization and their conquest of North America contribute immensely to the spreading of the language. This paper traces the historical spread of English as a language, the methods that were used to teach it across the ages and its adoption as a foreign language in Indonesia. It also examines its introduction to the senior high school and the effectiveness of the present curriculum. Findings show that the current program requires upgrading, while a lot of administrative adjustments are required to encourage students learning the language as part of the curriculum. It was further concluded that the only way to improve quality of graduates and make them useful in the international labor market is to incorporate English as part of the curriculum and as medium of teaching in Indonesia.